PRAKTEK TATA KELOLA PERTAMBANGAN RAKYAT DAN PEMANFAATAN HASIL TAMBANG PASCA BERLAKUNYA UU NOMOR 4 TAHUN 2009 TENTANG MINERAL DAN BATUBARA - Lodofikus Roe (Program Magister Ilmu Hukum Universitas Pancasila, 2018)
Community activities that mine today cannot yet be classified as a People's Mining activity(PR), as referred to in the applicable laws and regulations. This is due to not fulfilling theprovisions, both legal aspects and technical aspects that refer to the concept of goodpractice. The community activities that have been going on for hundreds of years have causedmany problems and losses, both for the state, the environment and for themselves. The natureof activities that are generally of the state has been detrimental to the state's income, while theenvironmental damage they have caused has caused long-term loss of ecosystems. Threenational priorities emerge. First, that people's mining includes mining activities in generalwhich have been regulated in mineral and coal laws Second, that Mining Without Permit(PETI) is prohibited according to mineral and coal laws. Third, that from the case studyactivities against violations of the precautionary principle or early prevention by PTIndominco Mandiri proving that there is no principle of early prevention in mining practices